HANS STADEN AND THEREAFTER - Gandara, Paula (Revista Literatura em Debate, 2014)
Hans Staden’s book Hans Staden, The True History of His Captivity is responsible for the development and growth of the idea of anthropophagy in Brazil to this day. In this article we will explore its historical and social relations with modern Carnival in Brazil while paying special attention to Mikhail Bakhtin and Roberto da Matta’s theories.